2021
DOI: 10.3390/pharmaceutics13111954
|View full text |Cite
|
Sign up to set email alerts
|

Nanodispersions of Polyelectrolytes Based on Humic Substances: Isolation, Physico-Chemical Characterization and Evaluation of Biological Activity

Abstract: Natural polyelectrolytes, including in the form of complexes with colloidal particles, are increasingly used in pharmacy due to the possibility of regulated attachment of medicinal substances and their targeted delivery to the target organ. However, the formation, stability, and molecular-mass characteristics of polyelectrolyte nanodispersions (ND) vary depending on the nature and composition of the medium of their origin. This is due to the lack of standardized approaches to quality control and regulatory doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 92 publications
0
13
0
Order By: Relevance
“…Other studies in the literature have also used HS or FA as therapeutic element carrying agents in cell culture against SARS-CoV-2. Uspenskaya et al found that the half maximal inhibitory concentration (IC 50 ) of natural HS is 0.023–0.041 mg/mL during the treatment of Vero E6 cell culture against SARS-CoV-2 virus [ 57 ]. Köntös discovered that 200 μg/mL concentration of iodine-fulvic acid clathrate complex reduced the infectious dose of SARS-CoV-2 to 1% of its original value using Vero 76 cell culture [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies in the literature have also used HS or FA as therapeutic element carrying agents in cell culture against SARS-CoV-2. Uspenskaya et al found that the half maximal inhibitory concentration (IC 50 ) of natural HS is 0.023–0.041 mg/mL during the treatment of Vero E6 cell culture against SARS-CoV-2 virus [ 57 ]. Köntös discovered that 200 μg/mL concentration of iodine-fulvic acid clathrate complex reduced the infectious dose of SARS-CoV-2 to 1% of its original value using Vero 76 cell culture [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The exact molecular mechanism of the antiviral effect of HSs is not yet clear. A recent study supposes that natural HSs samples as polyelectrolytes can block the interaction between coronaviral spike glycoproteins and cell membrane receptors [ 57 ]. In presenting indirect, host-related antiviral action, HSs can directly suppress oxidative stress, by recombination with intermediate free radicals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of humic–fulvic acid was received from the Sistema Biotechnologii company as previously described [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Biological polyelectrolytes (PECs), also called biological polyelectrolyte complexes, generally comprise strong intermolecular interactions known as Coulomb’s interactions or electrostatic interactions between oppositely charged groups, e.g., cationic biopolymers such as chitosan [ 1 ], poly-l-lysine [ 2 ], poly-L-arginine [ 3 ], insulin [ 4 ], collagen [ 5 ], amino dextran, and 2-(diethylamino) ethyl dextran [ 6 ] with anionic biopolymers such as pectin [ 7 ], alginate [ 8 ], xanthan gum [ 1 ], dextran derivatives [ 6 ], hyaluronic acid [ 9 ], carrageenan [ 1 ], neem gum [ 10 ], heparin [ 11 ], chondroitin sulfate [ 12 ], carboxymethyl cellulose [ 13 ], humic substances [ 14 ], poly(γ-glutamic acid) [ 15 ], DNA [ 16 ], and siRNA [ 17 ]. Surfactant systems are generally used to prepare different polymeric systems, including spherically shaped polymeric particles at different sizes.…”
Section: Introductionmentioning
confidence: 99%